Composting to save the soil - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
PRONAT, the Protecffon of Nature team of ENDA (organizahon for Environment and Development in Africa) is operating a scheme to train Senegalese farmers in the use of compost in improving crop yield and soil productivity, in order to limit the...